2016
DOI: 10.1038/srep28519
|View full text |Cite
|
Sign up to set email alerts
|

Prostacyclin reverses the cigarette smoke-induced decrease in pulmonary Frizzled 9 expression through miR-31

Abstract: Half of lung cancers are diagnosed in former smokers, leading to a significant treatment burden in this population. Chemoprevention in former smokers using the prostacyclin analogue iloprost reduces endobronchial dysplasia, a premalignant lung lesion. Iloprost requires the presence of the WNT receptor Frizzled 9 (Fzd9) for inhibition of transformed growth in vitro. To investigate the relationship between iloprost, cigarette smoke, and Fzd9 expression, we used human samples, mouse models, and in vitro studies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…Early stages of lung premalignancy are also regulated by miRNA, making them potentially relevant to prostacyclin chemoprevention (8,13). While very little is known about prostacyclin or PPARγ and miRNA, we demonstrated that reduction of miR-31 occurs with prostacyclin treatment and may be linked to expression of the presumed iloprost receptor in the lung epithelium (14,15).…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…Early stages of lung premalignancy are also regulated by miRNA, making them potentially relevant to prostacyclin chemoprevention (8,13). While very little is known about prostacyclin or PPARγ and miRNA, we demonstrated that reduction of miR-31 occurs with prostacyclin treatment and may be linked to expression of the presumed iloprost receptor in the lung epithelium (14,15).…”
Section: Introductionmentioning
confidence: 75%
“…In the one-week smoke exposed model, mice are harvested after one week of smoke exposure or ambient air. After one week of smoke, FVB mice have early gene expression changes associated with lung cancer but do not yet have lesions (14). With smoke exposure, Snail, Vimentin, and COX-2 increase, while Ecadherin, CRB3, and PPARγ, decrease (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations